Assessment of landscape-scale fluxes of carbon dioxide and methane in subtropical coastal wetlands of South Florida - Delaria, Erin Rose; Wolfe, Glenn; Blanock, Kaitlyn; Hannun, Reem; Thornhill, Kenneth L.; Newman, Paul A.; Lait, Leslie; Kawa, Stephan Randolph; Alvarez, Jessica; Blum, Spencer; Castañeda-Moya, Edward; Holmes, Christopher D.; et al. (My University, 2024)
Coastal wetlands play a significant role in the storage of ‘bluecarbon’, indicating their importance in the carbon biogeochemistry inthe coastal zone and in global climate change mitigation strategies. Wepresent airborne eddy-covariance observations of CO2 and CH4 fluxescollected in southern Florida as part of the NASA BlueFlux missionduring April 2022, October 2022, February 2023, and April 2023. The fluxdata generated from this mission consists of over 100 flight hours andmore than 6000 km of horizontal distance over coastal saline andfreshwater wetlands. We find that the spatial and temporal heterogeneityin CO2 and CH4 exchange is primarily influenced by season, vegetationtype, ecosystem productivity, and soil inundation. The largest CO2uptake fluxes of more than -20 µmol m-2 s-1 were observed over mangrovesduring all deployments and over swamp forests during flights in April.The greatest CH4 effluxes of more than 250 nmol m-2 s-1 were measured atthe end of the wet season in October 2022 over freshwater marshes andswamp shrublands. Although the combined Everglades National Park and BigCypress National Preserve region was a net sink for carbon, CH4emissions reduced the ecosystem carbon uptake capacity (net CO2 exchangerates) by 11-91%. Average total net carbon exchange rates during theflight periods were -4 to -0.2 g CO2-eq m-2 d-1. Our results highlightthe importance of preserving mangrove forests and point to potentialavenues of further research for greenhouse gas mitigation strategies.